Effects of wave passage on the relevant dynamic properties of structures with flexible foundation. - Aviles, Javier
An evaluation of the wave passage effects on the relevant dynamic properties of structures with flexible foundation is presented. A simple soil structure system similar to that used in practice to take into account the inertial interaction effects by the soil flexibility is studied. The kinematic interaction effects due to non-vertically incident P, SV and Rayleigh waves are accounted for in this model. The effective period and damping of the system are obtained by establishing an equivalence between the interacting system excited by the foundation input motion and a replacement oscillator excited by the free field ground motion. In this way, the maximum structural response could be estimated from standard free field response spectra using the period and damping of the building modified by both the soil flexibility and the travelling wave effects. Also, an approximate solution for the travelling wave problem is examined over wide ranges of the main parameters involved. Numerical results are computed for a number of soil structure systems to identify under which conditions the effects of wave passage are important. It comes out that these effects are generally negligible for the system period, but they may significantly change the system damping since the energy dissipation within the soil depends on both the wave radiation and the diffraction and scattering of the incident waves by the foundation.
Keywords: Soil structure interaction; Free field motion; Foundation input motion; Wave passage effects; System period; System damping